A clinicopathologic study on triple-negative breast cancer patients: HUSM experience - Saidin, Usman Sani (2011)
Breast cancer is the most common cancer among Malaysian women. There are many prognostic factors contributing to the disease and the outcome of the patients. Triple negative breast cancers are defined by a lack of expression of oestrogen, progesterone, and c erbB-2 receptors. They tend to have a higher grade with a poorer outcome compared to non-triple negative breast cancers. Hence, a retrospective study was carried out aiming to observe the association of triple negative (oestrogen receptor (ER), progesterone receptor (PR) and c erbB-2) breast cancer patients to the pathological (histological subtype, tumour grade, tumour size and lymph node involvement) and non pathological parameters (patient’s age and ethnicity). Twenty three cases of triple negative breast cancer among 115 cases of breast cancer diagnosed in three years (2002 to 2004) were reviewed. They represented 20.0% of total breast cancer patients. There were significant association between triple negative breast cancer with tumour size, lymph node involvement and lymphovascular invasion. However, age, race, histological subtype and histological grade did not show significant association. From these findings, we conclude that tumour size is the strongest factor associated with the triple negative breast cancer. Besides that, lymph node involvement is also associated with triple negative breast cancer. However, lymph vascular invasion is not associated with triple negative vascular breast cancer.